What’s New in Addiction Prevention in Young People: A Literature Review of the Last Years of Research - Cédric Kempf; Pierre-Michel Llorca; Pierre-Michel Llorca; Frank Pizon; Georges Brousse; Georges Brousse; Valentin Flaudias; Valentin Flaudias (Frontiers in Psychology, 2017)
Rationale: Addiction prevention is a major public health problem, particularly concerning young people. Despite the consensus that primary prevention is essential, the evaluation of its impact is questioned.Objective: The objective of this paper is to assess the latest knowledge of addiction prevention programs for young people.Method: Review a collection of research articles using a keyword-based search on three databases: Pubmed, Eric, and PsycInfo. The research was carried out using three groups of keywords and the eligibility study was completed using two criteria: articles published between 2010 and 2017, and articles in refereed journals.Results: Of a total of 13,720 articles in the three databases, 32 studies were included in the review and listed in a grid with five themes: authors, type of population, total population, addictive behavior, and results. Four categories were created based on the objective of the studies: the evaluation of prevention strategies, the study of risk factors for consumption, the prevalence study and other subjects studied. The analysis of the corpus was used to establish a list of risk factors to be taken into consideration in future interventions and research. A list of key elements for performing effective interventions and future research is also proposed.Conclusion: The understanding of the prevention strategies implementation process is discussed as a central element for future research, which will combine stakeholders and researchers. The complexity of the situations and the multifactorial aspects of addiction prevention in young people require a multidisciplinary approach involving the various stakeholders and researchers.